AI-Powered Chatbots for Mobile Teacher Training: Enhancing Interactive Learning Experiences - Ahmad, Fadi Bani (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The study aims to explore the impact of artificial intelligence (AI)-powered chatbots in mobile teacher training, specifically in enhancing interactive learning. To achieve the objective, the researcher employed an experimental approach using a single-group (pre-post) design. The study sample consisted of 50 male and female secondary school teachers who received training based on chatbot applications over a four-week period. Following the training, the research instrument—a teaching skills scale was administered. This scale measured three key skills: interactive planning, the integration of technology in teaching, and interactive evaluation. The results revealed statistically significant differences between the participants’ scores on the teaching skills scale in the pre- and post-tests across all dimensions and the overall score. These differences favored the post-test results, indicating an improvement after exposure to the chatbot-based training program. Considering these findings, the study recommends the development of ongoing professional training programs for teachers, particularly those incorporating innovative models such as chatbot applications.